High concentrated etoposide solutions, additional physical stability data in dextrose 5%. Issue 4 (20th October 2020) - Ravey, Marine; Polo, Caroline; D'Huart, Elise; Vigneron, Jean; Demoré, Béatrice
Abstract : Objectives: According to the manufacturers, the concentration of etoposide solutions should not exceed 0.4 mg/mL due to a risk of precipitation. Stability studies at higher concentrations were conducted and notably demonstrated 28 day stability up to 1.75 mg/mL for etoposide solutions in 5% dextrose (D5W). Nevertheless, colleagues report precipitation even at 0.4 mg/mL in their daily practice. The objective of this work was to reassess the physical stability of highly concentrated etoposide solutions in D5W (1.2 mg/mL), over a large number of preparations and under different manufacturing processes. Methods: To study the impact of manufacturing process, etoposide was taken with a spike or a needle and injected in three types of D5W containers (Easyflex, Viaflo and Ecoflac). Forty preparations were made for each container. For half of the preparations, a homogenisation was performed by a syringe rinse. Physical stability was realised by two examiners, with a visual examination searching for the appearance of a precipitate, daily during the first week, then twice a week until day 56. Results: Hundred and eighteen solutions were clear and colourless. Precipitates were observed for two solutions: one in an Easyflex bag on day 4 and one in an Ecoflac container on day 35. Conclusions: The physical stability at 1.2 mg/mL in D5W remains validated. Precipitations are rare and concern less than 2% of preparations. The appearance of a precipitate does not seem to be correlated to the kind of container or manufacturing process. A rinse was performed for these two solutions to assess a mechanical pressure effect more important on the solution, which could lead to a higher risk of precipitations. However, this is not observed in our daily practice, especially at lower concentrated solutions. We only recommend using an administration set with an in-line micro-filter as a precaution in case of precipitations.